Industri Pengolahan Menyelamatkan Perekonomian Kota Ternate di Masa Pandemi Covid-19 - Hasonangan Siregar; Nursalamah Nursalamah; Asmul Fauzi; Arsidin Batubara (STIKes Ibnu Sina Ajibarang, 2024)
The leading sectors are almost in every region, including the provinces in Eastern Indonesia. In 2020, it can be seen that there are still 5 provinces in Eastern Indonesia with a GRDP value below Rp. 100,000 billion and North Maluku Province being the province in Eastern Indonesia with the lowest GRDP. This research is a quantitative research, the source of data in this research is secondary data. Data collection technique is documentation through published reports on the official website of the Central Statistics Agency, which is obtained through the official BI website www.bps.go.id. The data analysis technique used shift share analysis. Based on the results of the study, it can be concluded that the processing industry of Ternate City has endurance and grows positively during the COVID-19 pandemic.